Resilient Cities urban nutrition profile: Ethiopia - Margolies, Amy; Amunga, Dorcas; Zerfu, Taddese Alemu; Ruel, Marie T.; Olney, Deanna K. (International Food Policy Research Institute, 2024)
Key Messages -Undernutrition has declined over time, but stunting still affects 40 percent of rural children and 25 percent of urban children. -Micronutrient deficiencies—especially deficiencies in folate, zinc and Vitamin D—are a critical concern, particularly for urban women and girls. -Dietary quality is low in both rural and urban areas: while urban diets are moderately more diverse than rural ones, rising consumption of unhealthy foods is more of a concern than in rural areas at this time. -The cost of consuming a healthy diet in Ethiopia increased from US $2.83 to $3.72 from 2017—2022, and over half of the population is currently unable to afford a healthy diet. -Concurrent conflict and climate shocks are causing acute nutritional needs in some regions. Humanitarian food aid is key to reducing food insecurity and should be provided to households without access to land who rely on income for food purchases, such as those in urban areas. -Overweight and obesity are still uncommon among young children but are increasing rapidly among urban women. In urban areas, 20 percent of women are overweight, compared to 4 percent in rural areas. The rise in urban overweight is driven by lifestyle changes associated with urbanization and unhealthy food environments, which are associated with poor quality diets and reduced physical activity. -Overnutrition and diet-related noncommunicable diseases are especially prevalent in Addis Ababa. -Food safety is a challenge, and evidence is lacking on how to improve vendor safety knowledge and practices to protect consumer health. -National social protection programs often fail to reach the urban poor and lack explicit nutrition interventions in urban areas. -There is a need to design and test urban nutrition interventions that address both over and undernutrition (such as double-duty actions) in urban populations.